Michael Walzer's Just War Theory: Some Issues of Responsibility - Primoratz, Igor (2002)
In his widely influential statement of just war theory, Michael Walzer exempts conscripted soldiers from all responsibility for taking part in war, whether just or unjust (the thesis of the “moral equality of soldiers”). He endows the overwhelming majority of civilians with almost absolute immunity from military attack on the ground that they aren't responsible for the war their country is waging, whether just or unjust. I argue that Walzer is much too lenient on both soldiers and civilians. Soldiers fighting for a just cause and soldiers fighting for an unjust one are not morally equal. A substantial proportion of civilians in a democracy are responsible, to a significant degree, for their country's unjust war. Moreover, under certain (admittedly rare) circumstances, some of them are legitimate targets of military attack. This has bearing on settling moral accounts in the wake of war and the issue of forgiving the wrongs done in its course: possible candidates for such forgiveness are much more numerous than is usually assumed.
Keywords: War; responsibility of; Soldiers; Just War Theory; ethics of war; conscription; civilian immunity